2019
DOI: 10.1093/isq/sqz075
|View full text |Cite
|
Sign up to set email alerts
|

A Growing Queer Divide: The Divergence between Transnational Advocacy Networks and Foreign Aid in Diffusing LGBT Policies

Abstract: Despite years of success, lesbian, gay, bisexual, and transgender (LGBT) norms are becoming increasingly polarized across the global landscape—with some countries strongly complying with new expectations while others openly defy them. To explain these divergent paths, I investigate the transmission of global LGBT norms via two mechanisms: transnational advocacy networks and foreign aid conditionalities. In examining LGBT policy adoption across 110 non-Organisation for Economic Co-operation and Development (OEC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 92 publications
0
18
0
Order By: Relevance
“…This research has shown that the more ties to bilateral aid donors that states have, the more likely a country is to adhere to world society human rights norms and join international organizations (Swiss, 2016b). For instance, Velasco (2020) shows that countries receiving aid from more donor countries, and those receiving more aid overall are predicted to offer more protections to LGBT rights. Likewise, bilateral aid donors are more likely to provide aid to countries which are already more embedded in international networks (Swiss, 2017) or with whom they share more common memberships in international organizations (Swiss & Longhofer, 2016).…”
Section: Aid and The World Societymentioning
confidence: 96%
See 1 more Smart Citation
“…This research has shown that the more ties to bilateral aid donors that states have, the more likely a country is to adhere to world society human rights norms and join international organizations (Swiss, 2016b). For instance, Velasco (2020) shows that countries receiving aid from more donor countries, and those receiving more aid overall are predicted to offer more protections to LGBT rights. Likewise, bilateral aid donors are more likely to provide aid to countries which are already more embedded in international networks (Swiss, 2017) or with whom they share more common memberships in international organizations (Swiss & Longhofer, 2016).…”
Section: Aid and The World Societymentioning
confidence: 96%
“…Foreign aid's role in funding the diffusion and institutionalization of world society norms has only recently become a focus of research (Fejerskov, 2015;Peterson, 2014;Swiss, 2016bSwiss, , 2016cSwiss, , 2017Velasco, 2020). This research has shown that the more ties to bilateral aid donors that states have, the more likely a country is to adhere to world society human rights norms and join international organizations (Swiss, 2016b).…”
Section: Aid and The World Societymentioning
confidence: 99%
“…Despite this growing awareness of LGBT rights, countries vary greatly in their policy environments (Velasco, 2020). Based on available scholarship, we theorize opposing reasons for why country-of-origin policies might shape migration into the U.S. by same-sex couples.…”
Section: Our Interventionmentioning
confidence: 97%
“…First, we rely on American Community Survey (ACS) data for 2008 to 2019 (Ruggles et al, 2021), which allows the identification of same-sex couples, immigrant origin, U.S. state of residence, and potentially confounding individual characteristics. Second, we harness original datasets indexing LGBT policy changes in 193 countries and all U.S. states from 1991 to 2019 (Velasco, 2020). We merge these two primary data sources with countryand state-level control variables from the UN, World Bank, U.S. government, and other sources.…”
Section: Introductionmentioning
confidence: 99%
“…Or Lee's (2019) and Meyers's (2019) critical analyses of the notion of "thinking globally, acting locally," whereby rights-based universals meet resistant practices that challenge the universals. Or Velasco's (2020) analyses of LGBT rights-based norms and their diffusion through two different social organizational forms, transnational advocacy networks or bilateral foreign aid.…”
Section: Gendersmentioning
confidence: 99%